Rewilding and Forest Transition in Polish Carpathians: An assessment of the connectivity of potential wolf habitat patches for the period 1970 and 2013 - Hernando Hernando, Daniel Benith (2023)
Land abandonment and forest succession in the Polish Carpathians have led to varied impacts on the landscape, from biodiversity benefits to the loss of sociocultural agricultural practices. This study investigates the impacts of land abandonment and forest succession in the Polish Carpathians, focusing on forest regeneration and wolf repopulation from 1970 to 2013. The relationship between increasing forest cover and interface areas is examined. Wild-Urban (WUI), evaluating whether this forest growth provides suitable habitats for wolves. The research contemplates the interaction between forest expansion and human presence, highlighting how the proliferation of human settlements affects the suitability of habitats for large carnivores. Connectivity analyzes and optimal path algorithms are used to determine the interconnection between potential wolf habitats and WUI areas, thereby addressing habitat fragmentation in human-dominated landscapes. This work seeks to inform effective conservation strategies and contribute to the discourse on ecosystem restoration and renaturalization in Europe.